2022
DOI: 10.3390/molecules27072353
|View full text |Cite
|
Sign up to set email alerts
|

Smart Titanium Wire Used for the Evaluation of Hydrophobic/Hydrophilic Interaction by In-Tube Solid Phase Microextraction

Abstract: Evaluation of the hydrophobic/hydrophilic interaction individually between the sorbent and target compounds in sample pretreatment is a big challenge. Herein, a smart titanium substrate with switchable surface wettability was fabricated and selected as the sorbent for the solution. The titanium wires and meshes were fabricated by simple hydrothermal etching and chemical modification so as to construct the superhydrophilic and superhydrophobic surfaces. The micro/nano hierarchical structures of the formed TiO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the past two years, some reported coating materials have possessed more beautiful and unique microstructures, such as core–shell and hollow structures , and flower-like and helical morphologies. In addition, the spherical morphology is still the most common, which is generally uniform. , Although these fascinating microstructures have been designed and presented in reported works, there is still a lack of explanation regarding the effects of morphology on the enrichment performance. This needs to be further explored.…”
Section: Spme In Environmental Analysismentioning
confidence: 99%
“…In the past two years, some reported coating materials have possessed more beautiful and unique microstructures, such as core–shell and hollow structures , and flower-like and helical morphologies. In addition, the spherical morphology is still the most common, which is generally uniform. , Although these fascinating microstructures have been designed and presented in reported works, there is still a lack of explanation regarding the effects of morphology on the enrichment performance. This needs to be further explored.…”
Section: Spme In Environmental Analysismentioning
confidence: 99%
“…It demonstrated that the transformation of surface wettability between SHL&UWSOB and SHB&SOL was necessary for versatile applications. [36][37][38][39]…”
Section: Superhydrophobic Nfmentioning
confidence: 99%
“…This Special Issue, entitled “Solid-Phase Microextraction and Related Techniques in Bioanalysis”, consists of 14 original, peer-reviewed papers written by research groups worldwide. The topics covered include headspace fiber SPME (HS-SPME) gas chromatography–mass spectrometry (GC-MS) [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ], HS-in-needle ME (HS-INME)-GC-MS [ 9 ], thin film SPME (TF-SPME) liquid chromatography–tandem mass spectrometry (LC-MS/MS) [ 10 ], magnetic solid-phase extraction (MSPE) LC-MS/MS [ 11 ], in-tube SPME (IT-SPME) LC-MS/MS [ 12 , 13 , 14 ] and IT-SPME LC-UV [ 15 ]. The samples analyzed include a wide range of plant-derived volatile organic compounds [ 2 , 3 , 4 , 5 , 6 , 7 ]; body odor from the skin [ 8 , 9 ]; metabolites from urine [ 10 ], plasma [ 11 ] and saliva [ 12 ] samples; biomarkers of exposure to tobacco smoke in hair [ 13 , 14 ]; and environmental estrogens in water [ 15 ].…”
mentioning
confidence: 99%
“…Finally, an IT-SPME method using extraction tubes filled with hydrophilic, superhydrophilic, superhydrophobic and UV-irradiated superhydrophilic Ti wires as sorbents was used for on-line IT-SPME LC-UV analysis of six estrogen-like hormones in water samples [ 15 ].…”
mentioning
confidence: 99%